Physicochemical characterization and emulsifying properties evaluation of RG-I enriched pectic polysaccharides from Cerasus humilis. (15th May 2021) - Zhang, Shikai; He, Ziyang; Cheng, Yue; Xu, Fangzhou; Cheng, Xinxin; Wu, Peng
Graphical abstract: Highlights: RG-I enriched pectic polysaccharides extracted from Cerasus humilis fruits (RPCF). RPCF is a high-methoxy acetylated pectin. RPCF forms a weak gel network that stabilizes the emulsions. RPCF can provide additional oxidation stability to the internal-phase of emulsion. RPCF demonstrates potential in forming sugar-free gel systems. Abstract: Rhamnogalacturonan I (RG-I) enriched pectic polysaccharides were extracted from Cerasus humilis fruits (RPCF, RG-I: 74.46 %). Structural characterization including FTIR, XRD, NMR, HPAEC and SEM demonstrated that RPCF was a high-methoxy acetylated pectin macromolecule with abundant arabinose and galactose side chains (DM: 53.41 %, MW: 1098 kDa, (Ara + Gal)/Rha: 5.37 %). RPCF afforded additional lipid oxidation stability for emulsions, and exhibited significantly better emulsification performance than citrus pectin. In addition, RPCF formed a weak gel network that stabilized the emulsions (G′ > G″). Interestingly, RPCF had behaviors that are divergent from those of commercial high-methoxy pectin because it demonstrated potential in forming sugar-free gels systems. Overall, Cerasus humilis is a new source of pectin rich in RG-I. RPCF can be used as a novel emulsifier with gelling and antioxidant effects, providing its alternative application as a natural emulsifier and rheological modifier in a wide range of products, including those with oil-in-water and low sugar.